Теоретико-методологічні детермінанти дослідження кордонів та пограничного простору - Верменич, Я. (Український історичний журнал, 2020)
Мета статті – осмислення проблеми дослідження кордонів і порубіжних територій у просторово-політичному, національно-регіональному, семантичному, екзистенційному й термінологічному вимірах. Наукові підходи. Традиційні підходи до вивчення кордонів базуються на постулатах геополітики. Сучасна геополітика надає великого значення формуванню історико-географічних образів погранич на основі злиття часових та просторових параметрів і їх відображення у відповідних знаках, символах. Концепт «хронотопу прикордоння» – часово-просторового континууму з пріоритетом часу – дає змогу простежити складну еволюцію розвитку пограниччя з урахуванням геополітичних впливів та напрямів міграційних процесів. Наукова новизна. Сучасні геополітичні реалії диктують необхідність пошуку нових пояснювальних моделей і, відповідно, – нової наукової мови. Традиційні підходи, базовані на ідеях центральності й нормативності західної інтелектуальної традиції, сьогодні вже «не спрацьовують». Центри та периферії у сучасному світі стрімко міняються місцями, інтеграційні процеси супроводяться не менш помітними відцентровими. Порівняння, зв’язки, взаємообміни, перехресні впливи постають у вигляді фундаментальних опор для пошуку нових пояснювальних парадигм. Основний висновок. Не випадково у світі спостерігається підвищений інтерес до концептуалізації теоретичної лімології – науки про кордони. Упродовж другої половини ХХ й початку ХХІ ст. пройдено величезну відстань від класичних геополітичних підходів до некласичних антропологічних і новітніх – постнекласичних. Теоретична лімологія дедалі впевненіше прокладає собі шлях у систему освіти. Що ж до України, то в нас кордонознавство існує у кращому випадку у прикладному вимірі, а термін «лімологія» поволі приживається лише у предметному полі історичної та політичної регіоналістики. Саме тому концептуалізація нового наукового напряму має стати своєрідним викликом для історичної науки. Адже саме їй під силу створити таку модель ставлення до інакшості, яка утримуватиме соціум від нових розмежувань по лінії «наші – не наші». А також простежити на основі аналізу багатьох історичних колізій вплив «ефекту колії», залежності від пройденого шляху траєкторій майбутнього розвитку. The purpose of the article is to understand the problem of the study of borders and border areas in spatial-political, national-regional, semantic, existential and terminological dimensions. In its bitter experience, Ukraine has fully felt the flaw of a “borderline” strategy based on the conventionality of demarcation lines, at least in the north and east. Errors now have to be corrected in the face of real hostilities, which will require both much greater costs and longer periods of time. Scientific approaches. Traditional approaches to the study of borders are based on the tenets of geopolitics. Modern geopolitics attaches great importance to the formation of historical and geographical images of borders based on the confluence of temporal and spatial parameters and their representation in appropriate signs and symbols. The concept of “border chronotope” – a temporal-spatial continuum with a priority of time – makes it possible to trace the complex evolution of border development taking into account geopolitical influences and directions of migration processes. Scientific novelty. Modern geopolitical realities dictate the need to find new explanatory models and, accordingly, a new scientific language. Traditional approaches, based on the ideas of centrality and normativity of the western intellectual tradition, are no longer working. Centers and peripherals in the modern world are rapidly changing places, integration processes are accompanied by no less noticeable centrifugal ones. Comparisons, relationships, exchanges, cross-effects are the foundations of the foundations for finding new explanatory paradigms. The main conclusion of the author. It is no coincidence that there is an increasing interest throughout the world in the conceptualization of theoretical limology – the science of borders. During the second half of the twentieth and early twentieth centuries, there was a great distance from classical geopolitical approaches to non-classical anthropological and newest – post-classical. Theoretical limology is increasingly making its way into the education system. As far as Ukraine is concerned, border science exists at its best in the applied dimension, and the term “limology” is slowly being adopted only in the subject field of historical and political regionalism. That is why the conceptualization of a new scientific direction must be a unique challenge for historical science. Because it is for her to create such a model of attitude to otherness, which will keep society from new distinctions on the line “ours – not ours”. And also to trace on the basis of the analysis of many historical conflicts the influence of the “gauge effect”, depending on the path traveled trajectories of future development.